4 - Fanon and Development: A Philosophical Look: 10.4314/ad.v29i1.22186 - Gordon, Lewis R. (Africa Development, 2004)
This article examines concepts of imitation, theodicy, and immaturity in Fanon's ideas on development and explores how his critique unfolds in the thought of two scholars influenced by his work: Sylvia Wynter and Irene Gendzier. Wynter, working from a poeticist semiotic perspective, rejects development as a much limited concept premised upon European normativity and calls for building an epistemological revolution. Gendzier, through a genealogical historicist critique of development studies, substantiates Wynter's critique and argues that development studies reveals more about the First World than any others. The author then considers and issues a critique of Amartya Sen's recent effort to rescue development studies through his formulation of development as an economy of freedom. The rest of the article presents an Africana postcolonial phenomenological treatment of freedom as a dialectical relationship between the lived reality of choices and social options and the need for a radical humanistic globalism with which to fight contemporary neoliberal and conservative ones.